Makna Pluralitas Dalam Film â€œRaya And The Last Dragonâ€ (Studi Analisis Semiotika Roland Barthes) - Pujianti, Inne; Mulyana, Ahmad (Syntax Corporation, 2024)
Film is actually a text that shows social reality. The text contained in a film forms a meaning as well as reflects a certain culture. The messages conveyed in films can be informative as well as educational media for the audience, messages to introduce a culture, build a democratic society and films can also unite differences and construct social realities that occur in society. The author in this study looks at the differences in the meaning of pluralism in the film